Factors Associated with HIV Status Disclosure to Orphans and Vulnerable Children Living with HIV: Results from a Longitudinal Study in Tanzania. (28th December 2020) - Bajaria, Shraddha; Exavery, Amon; Toroka, Noreen; Barankena, Asheri; Charles, John; Kikoyo, Levina
Abstract : Background . The Tanzanian national guideline for pediatric HIV disclosure recommends beginning disclosure as early as age 4–6 years; full disclosure is recommended at the age of 8–10 years. Despite clear procedures, the disclosure rate in Tanzania remains relatively low. This study assessed the factors associated with HIV status disclosure to orphans and vulnerable children living with HIV (OVCLHIV). Methods . Data for this analysis come from the USAID-funded Kizazi Kipya program in Tanzania that provides health and social services to OVC and caregivers of HIV-affected households. Data were collected between January 2018 and March 2019. Disclosure status was self-reported by caregivers of children aged 8 years or above. Beneficiary characteristics were included as independent variables. Generalized estimating equations took into account the clustering effect of the study design. Results . Of the 10673 OVCLHIV, most were females (52.43%), and 80.67% were enrolled in school. More than half (54.89%) were from households in rural areas. Caregivers were mostly females (70.66%), three quarters were between 31 and 60 years old and had a complete primary education (67.15%), and 57.75% were HIV-infected. Most of the OVCLHIV (87.31%) had a disclosed HIV status. Greater OVCLHIV age p < 0.001, school enrollment (OR = 1.22; 95% CI 1.06, 1.41), urban location of household (OR = 1.64; 95% CI 1.44, 1.86), caregivers' higher education level p < 0.001, and caregiver HIV-positive status (OR = 1.25; 95% CI 1.09, 1.43) were positively associated with disclosure status. OVCLHIV of female caregivers were 27% less likely to have been disclosed than those of male caregivers. Conclusion . The disclosure rate among OVCLHIV in this study was high. Disclosure of HIV status is crucial and beneficial for OVCLHIV continuum of care. Caregivers should be supported for the disclosure process through community-based programs and involvement of health volunteers. Policymakers should take into consideration the characteristics of children, their caregivers, and location of households in making disclosure guidelines as adaptable as possible.